Nearer, my God : an autobiography of faith - Buckley, William F. 1925-2008 (William Frank) (Orlando, Florida : Harcourt Brace & Company, 1998)
This is the story of one man's faith, told with unrivaled reflection and candor. In highly personal terms, and with the wit and acuity for which he is renowned, William F. Buckley Jr., examines in searching detail the meaning of Christianity in his life, and how he has been shaped and sustained by his religious convictions. Buckley discusses vital issues of Catholic doctrine and practice, and outlines both the nature of faith and its essential role in life. A provocative and challenging contribution to the national interest in the nature of religion, Nearer, my God is sure to appeal to all readers who have felt the stirrings of their own religious faith.
Donación del Dr. Ricardo Arias Calderón.
Keywords: BUCKLEY, WILLIAM F., -- 1925-2008; PERIODISTAS